Little Women - "Alcott, Louisa" (Wordsworth Classics: Ware, 2012)
Presents Little Women, which describes the family life of the four March sisters living in a small New England community, and Good Wives, which is the story of the March sisters some three years later, when, as young adults, they must face up to the inevitable trials and traumas of everyday life in their search for individual happiness.
Keywords: English Fiction